2019
DOI: 10.3389/fpls.2019.00991
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Molecular Responses of Tolerant, Susceptible and Highly Susceptible Grapevine Cultivars During Interaction With the Pathogenic Fungus Eutypa lata

Abstract: Eutypa lata is the causal agent of eutypa dieback, one of the most destructive grapevine trunk disease that causes severe economic losses in vineyards worldwide. This fungus causes brown sectorial necrosis in wood which affect the vegetative growth. Despite intense research efforts made in the past years, no cure currently exists for this disease. Host responses to eutypa dieback are difficult to address because E. lata is a wood pathogen that causes foliar symptoms several ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 95 publications
(189 reference statements)
4
24
0
Order By: Relevance
“…However, no response observed in both phenotypes when analysed using the least stable gene (RH8). Our results agree with the findings of Cardot et al 45 , where elicitation of chitinase genes observed in tolerant than in susceptible varieties.…”
Section: Discussionsupporting
confidence: 94%
“…However, no response observed in both phenotypes when analysed using the least stable gene (RH8). Our results agree with the findings of Cardot et al 45 , where elicitation of chitinase genes observed in tolerant than in susceptible varieties.…”
Section: Discussionsupporting
confidence: 94%
“…2 B). Several studies [ 22 , 23 , 38 ] reported PR gene repression including PR3 and PR4 genes as an indication of a reduction in the plant’s self-defense mechanism, thereby facilitating the progression of the infection process within the plant. We observed repression of both the PR3 and PR4 genes in the highly susceptible phenotype, V. a .…”
Section: Discussionmentioning
confidence: 99%
“…The PR proteins can respond to both biotic and abiotic stresses and belongs to different classes as described by van Loon et al [ 22 ]. Numerous studies have described the selective expression of PR-protein encoding genes following infection with a wide range of pathogens, whether it is necrotrophic or biotrophic [ 23 26 ]. According to Piasecka et al [ 27 ] certain defensive secondary metabolites are strongly induced after pathogen infection.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, decrease of sugars we observed in the wood could thus also be explained by remobilization toward the leaves to better sustain the infection. In a recent study, Cardot et al [38] showed coordinated upregulation of the hexose transporter VvHT5 and cell wall invertase in leaves of the tolerant cultivar Merlot elicited by Eutypa lata, but not in the highly susceptible cultivar Ugni Blanc. Regulation of sugar availability thus seems crucial for plant tolerance to trunk diseases.…”
Section: Discussionmentioning
confidence: 97%